Big Data, Big Concerns: Ethics in the Digital Age. (18th January 2018) - Jurkiewicz, Carole L.
Abstract : The collection of data on citizens through digital portals is viewed by organizations as an opportunity to create value, leverage competitive advantage, and maximize productivity and efficiencies in service and product delivery. As a condition of accessing digital media, individuals implicitly agree to allow the collection of data they generate while on a site, as well as content on the devices used to access the sites, unless steps are taken to limit such access. The growth in the amount of data collected has increased exponentially and has vastly outpaced awareness of or concerns about privacy; liability; ownership; property rights; and ethical issues that are emerging as citizens become aware of the consequences of trading privacy for access. While dominant in the professional press, the scholarly literature has only just begun to investigate ethical issues in the age of big data. This treatise will outline the scope of the issues; emerging problems; key ethical considerations; and areas in critical need of research and development moving forward.